Rosetta Stone: A Consideration of the Dardenne Brothers' Rosetta - Cardullo, Bert (The journal of religion and film, 2002)
The Dardenne brothers' Rosetta has Christian overtones despite its unrelieved bleakness of tone. In fact, the titular heroine, a teenaged Belgian girl living in dire, subproletarian poverty, has much in common with Robert Bresson's protagonists Mouchette and Balthasar. Both Mouchette (1966) and Au hasard Balthasar (1966) are linked with Rosetta in their examination of the casual, gratuitous inhumanity to which the meek of this earth are subjected, and both films partake of a religious tradition, or spiritual style, dominated by French Catholics like Bresson, Cavalier, Pialat, and Doillon. Those who have argued that the Dardennes' film is merely a documentary-like chronicle of a depressing case choose to ignore this work's religious element, in addition to the fact that Rosetta, unlike Mouchette or Balthasar, is alive and in the good company of a genuine human spirit at the end.